Predicting Academic Performance with Applying Data Mining Techniques (Generalizing the results of two Different Case Studies) - Rozita Jamili Oskouei; Mohsen Askari (Computer Engineering and Applications Journal, 2014)
Several research works are attempted to predict students academic performance and assess  the  evaluating students knowledge  or  detecting  students’  weakness and probability of failure in final semester examinations. However, several factors affect the performance of students in different countries or even in different states of one country. Therefore, understanding these factors and analyzing the effects of each one of those factors in each country, is necessary for improving instructors’ decisions in selecting   the best teaching method for helping weak students or   increasing performance  of  other  students. This study is motivated  to  study  the  students’ academic performance in high  school  and  bachelor  degree  studies  in  Iran and comparing these analysis results with the similar study’s results in India.